2014
DOI: 10.1159/000360768
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Complications Associated with TORS for OSAHS: A Benchmark for Evaluating an Emerging Surgical Technology in a Targeted Application for Benign Disease

Abstract: Background: The aim of this study was to create benchmarks for evaluating clinical outcomes and complications of transoral robotic surgeries (TORS) in a multicenter setting. Methods: 243 TORS for obstructive sleep apnea/hypopnea syndrome (OSAHS) operations, carried out between 2008 and 2012, were analyzed at 7 different centers. The average hospitalization was 3.5 days. The mean patient age was 50 ± 12 years, the average BMI at the time of the procedure was 28.53 ± 3.87 and the majority of the patients were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(131 citation statements)
references
References 16 publications
(11 reference statements)
1
126
0
4
Order By: Relevance
“…With improved visualization and the ability to quantify the amount of tissue resected in real time, it appears that TORS-assisted lingual tonsillectomy offers some clear advantages to previous procedures. A large multicenter trial has shown the efficacy of TORS as part of a multilevel approach to obstructive sleep apnea is effective with an overall success rate of 67% [19]. …”
Section: Discussionmentioning
confidence: 99%
“…With improved visualization and the ability to quantify the amount of tissue resected in real time, it appears that TORS-assisted lingual tonsillectomy offers some clear advantages to previous procedures. A large multicenter trial has shown the efficacy of TORS as part of a multilevel approach to obstructive sleep apnea is effective with an overall success rate of 67% [19]. …”
Section: Discussionmentioning
confidence: 99%
“…They also found that the TORS result was significantly improved compared to radiofrequency ablation of the tongue base but not compared to submucosal minimally invasive lingual excision (SMILE). The largest series to date has recently been organized by Vicini et al [25]; this benchmark study included 7 centers from 5 countries. The results of 243 patients with at least 3 months of follow-up were analyzed retrospectively and again demonstrated both the safety and efficacy of the procedure (pre- vs. postoperative AHI 43.0 vs. 17.9, and pre- vs. postoperative ESS 12.3 vs. 5.7).…”
Section: Discussionmentioning
confidence: 99%
“…TORS has been shown to be an effective and safe procedure for the treatment of OSA in patients with hypertrophy of the BOT and floppy epiglottis 3 4 . A low rate of major complications, such as intra-operative or post-operative massive bleeding, has been reported 3 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this technique has gained popularity as an effective therapeutic option both for OSA and head and neck cancer 3 - 5 . The aims of our paper are: 1.…”
Section: Introductionmentioning
confidence: 99%